Consent in Shakespeare : what women do and don't in Shakespeare's Mediterranean plays and origin stories - Preeshl, Artemis (Abingdon, Oxon ; New York : Routledge, 2022)
"By examining how female characters speak and act during coming of age, engagement, marriage, and intimacy, 'Consent in Shakespeare' will enhance understanding about how and why women spoke, remained silent, or acted as they did in relation to their intimate partners in Early Modern and contemporary private and public situations in and around the Mediterranean. Consent in intimate relationships is front and center in the today's conversations. In this study, how Shakespeare's female protagonists and supporting characters respond verbally and physically in Shakespeare's comedies and sources from which he derived his plays in and around Mediterranean call for a re-examination of women's roles in Early Modern and contemporary cultures. This re-examination of the words that women say or do not say, and actions that women do or do not take, in Shakespeare's Mediterranean plays and his probable sources shed light on how Shakespeare's audiences might have perceived the Mediterranean cultural mores and norms. Assessment of source materials for Shakespeare's comedies set in the Balkans, France, Italy, the Near East, North Africa, and Spain suggests how women of diverse backgrounds communicated in everyday life and peak life experiences in the Early Modern era. Given Shakespeare's impact worldwide, this initiative to shift the conversation about the power of consent of female protagonists and supporting characters in Shakespeare's Mediterranean plays will further transform conversations about consent in class, board and conference rooms, and the international stage"--
Keywords: Shakespeare, William, -- 1564-1616 -- Characters -- Women; Women in literature; Agent (Philosophy) in literature; Sexual consent in literature; PERFORMING ARTS / General; DRAMA / Shakespeare; LITERARY CRITICISM / Shakespeare